Thermal Performance Evaluation of a Small-Scale Drying Machine for Palm Oil Mill Sludge - Jong, R. P.; Shayuri, M. I. A.; Yassin, A.; A. Kamaruddin, A. M. N. (International Journal of Integrated Engineering, 2023)
Malaysia is one of the major contributors of palm oil production globally with large amount of palm oil production. This has significantly contributed to large amount of palm oil mill effluent that eventually affect the environment. A small-scale drying machine for palm oil mill is evaluated on its thermal performance to assess the suitability of the machine to produce organic fertilizer from the palm oil mill sludge. Evaluation was performed with computational fluid dynamics simulation and experiment on design configuration options of the drying machine. The effect of air flow to the thermal performance was also studied in conjunction with the design configurations of the drying machine. The results showed promising potential of a design configuration over another in term of thermal performance and functionality.